El estrés como factor de riesgo laboral en los docentes de la unidad educativa “Urcuquí” - Tulcanaza Palacios, Carlos Roberto (2022)
At present, work stress can occur in various ways and in the development of any type of activity, one of them is the teaching activity, which is carried out by the teachers of the 'Urcuquí' Educational Unit, a research place where the The main objective is based on analyzing the risk factor against work stress in the teaching staff, to later carry out a preventive plan, taking into account its causes and levels. All this through the collection of information through tests related to the subject (work stress) and endorsed by national and international studies to consecutively carry out a documentary investigation that allows us to support an improvement plan applicable in the institution immediately and that allows us to obtain results in the medium term. After the investigative analysis, the causes are determined, as well as the levels of stress that are managed in the teachers of the U. E. Urcuquí, where it can be evidenced that they maintain manageable levels of psychosocial risk, as well as their affectation in some of the dimensions analyzed, these being some of the aspects to be taken into account within the action plan, which presents several application strategies to achieve an improvement or decrease in the levels of psychosocial risk through the application of workshops and activities related to the study theme.